2019
DOI: 10.33794/qjas.vol9.iss1.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pollen Grains and Growth Regulator NAA on Some Fruit Characterization of Date Palm Phoenix Dactylifera L Cultivar. Sultani

Abstract: This research was conducted in orchard belong to Al-Mahawel date palm station (Abo Sderah) / Ministry of Agriculture located in governorate of Babylon, during the season 2015-2016. Twenty four uniform date palm Phoenix dactylifera. L. Sultani cultivar were used , to study the effect of the pollinator type(P1: Ghannamiakhder , P2: Ghannamiahmer and P3:khukri ), the concentration of Naphthalene Acetic Acid NAA(0 , 50 and 100 ) mg.L-1 and their interaction on fruits setting up , fruits drop and some of physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…(198.15 cm 3 ) in 2019 season compared to control and other treatments. The results are in agreement of those reported by Aubied and Hamzah, 2019).…”
Section: Flesh Volume (Cm 3 )supporting
confidence: 93%
“…(198.15 cm 3 ) in 2019 season compared to control and other treatments. The results are in agreement of those reported by Aubied and Hamzah, 2019).…”
Section: Flesh Volume (Cm 3 )supporting
confidence: 93%
“…Therefore, pollen source (male trees) has significant effect on fruit yield (Omar et al, 2014). In addition pollen grains effected directly the quality and the quantity of the fruits (Soliman and Osman, 2001;Farag, 2012;Hafez et al, 2014;Aubied andHamzah 2019 andmonir, 2020). Generally it could be safely concluded that Male (1) or M (6) were superior to pollen Barhi date palm as increased significantly the studied fruit quality (Metaxenia) especially fruit set, bunch weight total yield, physical characters in most cases as compared to the other Males…”
Section: Discussionmentioning
confidence: 99%
“…The date palm tree is one of the sweetest, full nutrient, and oldest fruit crops in North America and the Middle East, especially in North African countries and Arabian Peninsula, had been cultivated about 7000 years ago (Flower et al, 2019) and have a vital character in commodities of daily life (Sallon et al, 2020). These fruit-bearing oldest trees grow well in different countries around the world in severe environmental conditions (Iubied and Hamzah, 2019). In the cultural heritage of the Arab region, the date palm possesses crucial significance in history being the most ancient, cultivated crop 3300-3100 BC (Paszke, 2019).…”
Section: Introductionmentioning
confidence: 99%